Seasonal Differences in Submicron Marine Aerosol Particle Organic Composition in the North Atlantic - Lewis, Savannah L.; Saliba, Georges; Russell, Lynn M.; Quinn, Patricia K.; Bates, Timothy S.; Behrenfeld, Michael J. (Frontiers in Marine Science, 2021)
Submicron atmospheric primary marine aerosol (aPMA) were collected during four North Atlantic Aerosol and Marine Ecosystem Study (NAAMES) research cruises between November 2015 and March 2018. The average organic functional group (OFG) composition of the aPMA samples was 72–85% hydroxyl group mass, 6–13% alkane group mass, and 5–8% amine group mass, which is similar to prior observations and to aerosol generated from Sea Sweep. The carboxylic acid group had seasonal averages that ranged from 1% for Winter, 8% for Late Spring, and 10% for Autumn. The carboxylic acid group mass concentration correlated with nitrate mass concentration and weakly with photosynthetically active radiation (PAR) above 100 W m–2, suggesting a substantial secondary organic aerosol contribution in sunnier months. The three sizes of aPMA aerosol particles (<0.18, <0.5, and <1 μm) had the same four organic functional groups (hydroxyl, alkane, amine, and carboxylic acid groups). The aPMA spectra of the three sizes showed more variability (higher standard deviations of cosine similarity) within each size than between the sizes. The ratio of organic mass (OM) to sodium (OM/Na) of submicron generated primary marine aerosol (gPMA) was larger for Autumn with project average of 0.93 ± 0.3 compared to 0.55 ± 0.27 for Winter, 0.47 ± 0.16 for Late Spring, and 0.53 ± 0.24 for Early Spring. When the gPMA samples were separated by latitude (47–60°N and 18–47°N), the median OM/Na concentration ratio for Autumn was higher than the other seasons by more than the project standard deviations for latitudes north of 47°N but not for those south of 47°N, indicating that the seasonal differences are stronger at higher latitudes. However, the high variability of day-to-day differences in aPMA and gPMA composition within each season meant that seasonal trends in organic composition were generally not statistically distinguishable.